2001
DOI: 10.1002/app.1970
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of elastomer–resin mixtures used as friction materials

Abstract: ABSTRACT:This study looks at the thermal behavior of mixtures of nitrile-butadiene rubber (NBR) with a resol or a novolac resin. When heated in the 200 -300°C range, NBR became hard and insoluble because of exothermic curing and cyclizing chain reactions involving the double bonds of its butadiene units and the nitrile groups of its acrylonitrile units. The NBR proved to be compatible with the novolac but not the resol. Heating increased the modulus of elasticity of the mixtures, which was due to crosslinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…These results suggest that the degradation temperature of the rubber/resin blend is dominated by the rubber component. Camino et al16 reported that the weight loss of NBR, degradation of NBR obtained by thermogravimetric analysis, begins at about 350°C, which is in agreement with the results obtained in this study. They16 also came into the same conclusion about the mixture of NBR and novolac PH, that the degradation temperature is dominated by NBR.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results suggest that the degradation temperature of the rubber/resin blend is dominated by the rubber component. Camino et al16 reported that the weight loss of NBR, degradation of NBR obtained by thermogravimetric analysis, begins at about 350°C, which is in agreement with the results obtained in this study. They16 also came into the same conclusion about the mixture of NBR and novolac PH, that the degradation temperature is dominated by NBR.…”
Section: Resultssupporting
confidence: 92%
“…Literature shows a limited number of studies devoted to the rubber/PH systems 14–16. In addition, the patents on this subject have provided a few technical details due to proprietary reasons 9–11.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 A typical semimetallic friction composite is composed of many ingredients, including metal, fillers, polymer matrix and abrasive particles. [11][12][13] Semimetallic friction composites have good performance, such as stable friction coefficient, high wear resistance and heat conductivity, low heat fade at high temperature and environment friendly components. 14,15 Therefore, they are widely used in the automobile industry at present.…”
Section: Introductionmentioning
confidence: 99%